Environmental Protection in Trade Agreements: A Critical and Constructive View of RCEP - Ly, Van Anh (Revue Interventions économiques / Papers in Political Economy, 2026)
Trade-Environment linkages have become a prominent phenomenon in contemporary global relations. From being treated as exceptions within the GATT/WTO framework and in earlier regional trade agreements (RTAs), environmental protection has been firmly integrated in multilateral progressive agenda as well as new-generation RTAs as shared obligations rather than as mere acknowledgments of states’ “right to protect”. This evolution demonstrates how trade agreements increasingly contribute to environmental goals. Yet, the recent Regional Comprehensive Economic Partnership agreement (RCEP) fails to appropriately address environmental provisions within its framework. This contrasts with the traditional environmental policies of the Association of Southeast Asian Nations, at the central of RCEP, as well as with the more progressive approaches adopted by nearly all RCEP members. By tracing the evolution of trade-environment linkages, highlighting selected RTAs concluded by RCEP members, this paper evaluates RCEP’s environmental aspect and offers forward-looking recommendations for more effectively embedding environmental objectives, in line with contemporary trends in sustainable trade governance.